Dialysis-Induced Immune Dysregulations and Their Possible Impacts on COVID-19 (Iranian Journal of Kidney Diseases, 2021)
Hemodialysis (HD) patients display metabolic and immunologic alterations that renders their immune responses to be dysregulated. These patients generally have problems in mounting effective immune responses against pathogens such as viruses. On the other hand they typically have higher levels of inflammatory cytokines in their peripheral blood. Both of these features may work in favor of COVID-19. Since robust immune responses are needed to prevent infection in the initial stages of COVID-19, the impaired immune system may not be able to cope effectively with the highly replicating SARS-CoV2. In advanced stages of the disease wherein the inflammation as well as the cytokine storm are the core players, a high baseline inflammatory cytokines could intensify and substantially exacerbate the immunopathological situation. Presence of COVID-19 in HD patients may also be a complex immunological condition. Immunological alterations in HD patients and their potential effects on the fate of the SARSCoV- 2 infection are discussed here. Case reports describing the occurrence of COVID-19 in HD patients have also been reviewed in this study.